BIOGRAPHY OF NATIVE CITY: A VIEW OF PRESCHOOL CHILDREN - Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article analyzes the peculiarities of perception of preschool children of their native city (for example, the city of Pskov). The author, based on OV Solntseva's experimental materials «Preschoolers about the city: from diagnosis to design the content of the pedagogical process» (2009-2010 years), gives the content and results of the self-study in the framework of the project "System of ethnocultural the education of children of preschool age in the border areas of Russia "(RFH, the project № 14-36-01242, 2014). The materials include the description of the experimental procedures, analysis of results of experimental study (ascertained experimental data), the findings underlying the construction of integrative technology of ethno-cultural education of children of preschool age on the content of architecture of their native city.